(untitled) (Journal of the College of Basic Education, 2022)
A field study aimed to know the position of professors of graduate in Jarrahs University of adoption of the seminar and its mechanisms as a way to approve the research plans for the students of Masters, and adopted the descriptive analytical method, research community was identified the, which consisted of (28) professor of Jarrahs University who are studying in the Master’s stage in six colleges which are covered by research, all of the research community Association has calculated research sample rate (100%). A questionnaire included 68 paragraphs was built. And the researchers made sure of its validity and reliability, and questionnaire was applied in the academic year 2014-2015, and statistical Pouch (SPSS) which was adopted showed the following results: that most of the research sample was of middle casting (3.359) and the weight percentage was (67.19%) which supported the seminar as a framework and entrance to the adoption of research plans for students and recommendation to reconsider the regulations and instructions adopted for the study of Masters in order to be compatible with the expected role of the seminar